PEDAGOGICAL APPROACHES IN MARITIME CADET TEACHING: ENHANCING LEARNING OUTCOMES - Mudakir; Boedojo Wiwoho Soetatmoko Jogo; Irene Evi Krismawati; Nyaris Pambudiyatno; Agus Dwi Santoso (Meteor STIP Marunda, 2024)
This research investigates pedagogical strategies in maritime cadet teaching to improve learning outcomes. Qualitative analysis involving 45 junior cadets from Maritime Institutes, Private Maritime Institutes, and Vocational Schools elucidates perceptions and effectiveness of teaching methodologies. Results highlight the importance of aligning pedagogy with international standards, addressing emerging needs, and fostering professionalism. Integrating emerging technologies, enhancing soft skills development, promoting safety culture, and continuous professional development emerge as crucial areas. The study emphasizes the significance of cultivating professionalism, including ethics, integrity, teamwork, leadership, and cultural sensitivity. Overall, this research emphasizes the necessity for continuous improvement and innovation in cadet training to prepare future maritime professionals effectively.